Tungsten (W) Laminate Pipes for Innovative High Temperature Energy Conversion Systems. Issue 4 (7th July 2014) - Reiser, Jens; Rieth, Michael; Möslang, Anton; Greuner, Henri; Armstrong, David E. J.; Denk, Thorsten; Gräning, Tim; Hering, Wolfgang; Hoffmann, Andreas; Hoffmann, Jan; Leiste, Harald; Mrotzek, Tobias; et al.
<x xml:space="preserve">Abstract</x> The aim of this paper is to present the mechanical properties of tungsten laminate pipes made of tungsten foil and to discuss their use in innovative high temperature energy conversion systems. Tungsten is the metal with the highest melting point of all metals and would therefore be an excellent fit for high temperature applications. But tungsten has one major drawback which is its low fracture toughness at room temperature (RT) or its high brittle‐to‐ductile transition temperature (BDTT). However, one of the extraordinary properties of tungsten is that by cold working the BDTT can be shifted to lower temperatures. At the extreme, these results in a tungsten foil with a BDTT below −120 °C combined with an RT fracture toughness of 70 MPa m1/2. By rolling up and joining a tungsten foil, tungsten laminate pipes can be synthesized that can dissipate at least 20 J in a Charpy impact test at RT and survive a burst test at RT at 1000 bar without any residual damage. The technical maturity of these W laminate pipes is approved by high heat flux tests performed at the Plataforma Solar de Almería, Spain, as well as at the Max Planck Institute of Plasma Physics, Garching, Germany.